THE ULTIMUM REMEDIUM PRINCIPAL FORMULATION POLICY IS PARTIAL IN NATURE IN CORPORATE CRIMINALITY IN INDONESIA - Adhari, Ade; Pujiyono, Pujiyono; Sidharta, Sidharta; Aprilia, Indah Siti (Indonesia Law Review, 2024)
This article identifies and examines the policy formulation of the ultimum remedium principle in criminalizing corporations in Indonesia. The source of criminal law is found in the Criminal Code (KUHP) and laws outside the Criminal Code. The principle of ultimum remedium in corporate punishment is not recognized in the Criminal Code. Limited ultimum remedium-based corporate penalties are found in various laws containing offenses in the fields of taxation, customs, excise and the environment. Normatively, the process of prosecuting a corporation is a last resort, and the main step required is fulfilling the obligation to pay off losses to state revenue, paying off import duties that are not or underpaid or after paying off excise that is not and/or underpaid. From this policy formulation, it can be seen that the principle of ultimum remedium in corporate punishment is partial.